Teachers’ Understanding of Formative Assessment - Arrafii, Mohammad Arsyad; Sumarni, Baiq (Bina Nusantara University, 2018)
The research explored teachers’ understanding of formative assessment in the secondary school level, particularly in the context of English teaching and examined factors related to the teacher assessment in the literacy level. To achieve the intended purposes, a self-designed instrument named Teacher Formative Assessment Literacy Questionnaire (TFALTQ) was emploted. Cronbach alpha measured the internal consistency of items that measuring the latent constructs were adequately accepted (α= 0,67), and exploratory the factor analysis using rotation matric revealed a robust factor loading of the variance explained with KMO statistic of 0,72. The questionnaire was distributed to all English teachers who taught in the secondary high school in central Lombok. There were 243 teachers from public and private high schools were participated in the study. The participants came from both public school and religious school, regardless of their school types and level. Using the case of 243 English teachers, the analysis reveals that the teachers’ understanding of formative assessment is inadequate and that four dimensions of teachers’ formative assessment literacy and understanding are revealed. These include an assessment to serve the accountability purpose, examination/test driven learning, the procedural approach to learning and assessment, and the receptive role of students. The multiple hierarchical regression analysis is performed to identify athe factors that are influencing the teachers’ formative assessment literacy. The analysis suggests that the teachers have a poor understanding of formative assessment, insufficient training in assessment and gender is a strong predictors of teachers understanding of formative assessment.